Edificio de viviendas - Caram-Robinsohn (2004)
Edificio de 36 vivienda en dúplex en Palermo, Buenos Aires, Argentina
Keywords: CARAM, ESTEBAN; ROBINSOHN, GUSTAVO; ARGENTINA; VIVIENDAS MULTIFAMILIARES; EDIFICIOS DE VIVIENDAS; BUENOS AIRES; DUPLEX; PALERMO